Sexuality in fishes - Pandian. T. J. (CRC Press ; Science Publishers, 2011)
The unprecedented level of diversity recorded among the clones of self-fertilizing gynogenetic unisexuals and self-fertilizing simultaneous hermaphrodites challenges current ideas on the predominant role of recombination in promoting evolution of biological diversity. This book offers a synthesis of relevant information on sexuality of fishes